2018
DOI: 10.1186/s12911-018-0657-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of predictive methods for early assessment of compliance with continuous positive airway pressure therapy

Abstract: BackgroundPatients suffering obstructive sleep apnea are mainly treated with continuous positive airway pressure (CPAP). Although it is a highly effective treatment, compliance with this therapy is problematic to achieve with serious consequences for the patients’ health. Unfortunately, there is a clear lack of clinical analytical tools to support the early prediction of compliant patients.MethodsThis work intends to take a further step in this direction by building compliance classifiers with CPAP therapy at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…A study from Spain found that there were four predictors for CPAP compliance, including headache, psychological symptoms, hypertension, and quality of life [17]. In our study, only fatigue was an independent predictor for good CPAP compliance.…”
Section: Discussionsupporting
confidence: 53%
“…A study from Spain found that there were four predictors for CPAP compliance, including headache, psychological symptoms, hypertension, and quality of life [17]. In our study, only fatigue was an independent predictor for good CPAP compliance.…”
Section: Discussionsupporting
confidence: 53%
“…According to previous studies on comorbidities and long-term compliance, hypertension is not an important predictor of long-term compliance; however, recently, Rafael-Palou et al [ 25 ] reported that hypertension was closely related to compliance at 1–3 months [ 26 , 27 ]. Our study confirmed these findings through between-group comparisons and multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital lung specialists managing these patients and the CPAP provider (Oxigen salud) also had access to the MiSAOS website that provided relevant information and decision support according to the specific role and access rights of each professional user. Finally, the cloud-based MiSAOS platform connected all the devices for data exchange and hosted an intelligent monitoring system, based on machine learning, capable of predicting the expected compliance with the therapy by a given patient, thus providing adequate feedback and proposing personalized interventions to increase compliance [ 15 , 18 ]. Predictions of patient’s midterm compliance were based on patient’s characteristics, such as anthropometric data and clinical information, and early compliance data.…”
Section: Methodsmentioning
confidence: 99%